The INFLUENCE OF BRAND IMAGE AND PRODUCT KNOWLEDGE ON PURCHASE DECISIONS (Study on Holland Bakery Pandanaran Semarang Consumers) - Sarah Puspaningrum; Handojo Djoko Walujo (Penerbit Jurnal Indonesia, 2021)
Bread is one of the favourite foods liked by most of people. Although bread is not a staple food, the business in the field of bread has a great potential, so many companies are opening their businesses in this field. This leads to intense competition between business companies. Holland Bakery as one of the first modern bakeries in Indonesia that has been established since 1978, continues to implement its marketing strategy to attract consumers and retain existing customers. This research aims to find out the influence of brand image and product knowledge on purchase decision (study on consumer of Holland Bakery Pandanaran Semarang). This type of research is explanatory research with nonprobability sampling techniques. The samples used for this research are 100 respondents. Data analysis techniques used in this are simple and multiple linear regression test. The result of this research shows that brand image has a significant effect on purchase decision, product knowledge has a significant effect on purchase decision, and brand image and product knowledge have a significant effect on purchase decision.